Standardized End Point Definitions for Coronary Intervention Trials: The Academic Research Consortium-2 Consensus Document - Garcia-Garcia, Hector M; McFadden, Eugène P; Farb, Andrew; Mehran, Roxana; Stone, Gregg W; Spertus, John; Onuma, Yoshinobu; Morel, Marie-Angèle; van Es, Gerrit-Anne; Zuckerman, Bram; Fearon, William F; Taggart, David; et al. (Circulation (New York, N.Y.), 2018)
The Academic Research Consortium (ARC)-2 initiative revisited the clinical and angiographic end point definitions in coronary device trials, proposed in 2007, to make them more suitable for use in clinical trials that include increasingly complex lesion and patient populations and incorporate novel devices such as bioresorbable vascular scaffolds. In addition, recommendations for the incorporation of patient-related outcomes in clinical trials are proposed. Academic Research Consortium-2 is a collaborative effort between academic research organizations in the United States and Europe, device manufacturers, and European, US, and Asian regulatory bodies. Several in-person meetings were held to discuss the changes that have occurred in the device landscape and in clinical trials and regulatory pathways in the last decade. The consensus-based end point definitions in this document are endorsed by the stakeholders of this document and strongly advocated for clinical trial purposes. This Academic Research Consortium-2 document provides further standardization of end point definitions for coronary device trials, incorporating advances in technology and knowledge. Their use will aid interpretation of trial outcomes and comparison among studies, thus facilitating the evaluation of the safety and effectiveness of these devices.